2016
DOI: 10.4103/0019-5413.193482
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of distal end radius in the Indian population: A radiological study

Abstract: Introduction:The morphometry of distal end radius (DER) comprises the four necessary parameters: radial inclination, palmer tilt, radial height, and ulnar variance. The unblemished intellect about the morphometry is urged for the management of fracture of DER. The goal of our study was to determine the values of morphometric parameters of the DER from the adult Indian.Materials and Methods:It was a single hospital- based observational cross-sectional, prospective study. Radial inclination, radial height, and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 20 publications
6
19
1
2
Order By: Relevance
“…Chan et al [2] observed that the mean ulnar variance was a positive variance of 0.13 ± 0.72mm. Mishra et al [11] in their study of the Indian population observed a positive ulnar variance if 0.66 ±2.46mm [10]. However in our study there was a higher tendency was negative ulnar variance (Tables 6,7).…”
Section: Introductioncontrasting
confidence: 54%
See 3 more Smart Citations
“…Chan et al [2] observed that the mean ulnar variance was a positive variance of 0.13 ± 0.72mm. Mishra et al [11] in their study of the Indian population observed a positive ulnar variance if 0.66 ±2.46mm [10]. However in our study there was a higher tendency was negative ulnar variance (Tables 6,7).…”
Section: Introductioncontrasting
confidence: 54%
“…In our study, only the radial height showed a statistical difference between the male and female population. Mishra et al also ob- served a similar statistical difference in the radial height between genders [11]. The earliest effect of malunited distal radius fractures, on the normal biomechanics of the wrist joint, was described by Gartland and Werley in 1951 [8].…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Nevertheless, these difficulty will be reduced when country specific normative data are made available. [14,21] Capitolunate angle and scapholunate angle In this study, the CLA and SLA had a range of 14º to 22º and 35º to 55º respectively, which fell within the normal range reported by Gilula and Chesaru and Tischler et al [7,22] Values above the reported range suggests a scapholunate advanced collapse is characterised by abnormal increase in the scapholunate interval and forward movement of the capitate bone and characteristic tilting towards the dorsum of the scaphoid bone (Chang et al, 2014). [23] Radial tilt This studied population had a radial tilt range of 10-21º which was within the normal range of 11º (range; 2-20°) reported by Smithuis.…”
Section: Side Differencementioning
confidence: 99%